Enterprise Size, Financing Patterns, and Credit Constraints in Brazil : Analysis of Data from the Investment Climate Assessment Survey - Kumar, Anjali; Francisco, Manuela (Washington, DC: World Bank, 2012)
Enterprise Size, Financing Patterns, and Credit Constraints in Brazil investigates the importance of firm size with respect to accessing credit. The principal findings are that size strongly affects access to credit compared to firm performance, and other factors, such as management education, location or the industrial sector to which the firm belongs. Additional findings are that the impact of size on access to credit is greater for longer term loans and that public financial institutions are more likely to lend to large firms. Finally, financial access constraints may have a less significant differential impact across firms of different sizes than other constraints, though cost of finance as a constraint is very important.